Penile Glans Necrosis Developing after Internal Pudendal Arterial Embolization: A Case Report - Kim, Tae Nam; Lee, Chan Ho; Baek, Seung Ryong; Lee, Kyung Min; Choe, Sangmin; Park, Nam Cheol; Park, Hyun Jun (Urology Journal, 2018)
Penile glans ischemia or necrosis developing after internal pudendal arterial embolization is very rare; no relevant report has yet appeared. A 53-year-old male who visited our emergency room because of massive urethral bleeding was diagnosed with an internal pudendal artery-urethral fistula; he underwent selective embolization of the internal pudendal artery. However, unexpected penile glans ischemic necrosis developed after embolization. We successfully treated the patients with intravenous infusion of alprostadil, oral pentoxifylline and tadalafil.